Nucleus Accumbens Core Dopamine D2 Receptor-Expressing Neurons Control Reversal Learning but Not Set-Shifting in Behavioral Flexibility in Male Mice - Macpherson, Tom; Kim, Ji Yoon; Hikida, Takatoshi (Frontiers in Neuroscience, 2022)
The ability to use environmental cues to flexibly guide responses is crucial for adaptive behavior and is thought to be controlled within a series of cortico-basal ganglia-thalamo-cortical loops. Previous evidence has indicated that different prefrontal cortical regions control dissociable aspects of behavioral flexibility, with the medial prefrontal cortex (mPFC) necessary for the ability to shift attention to a novel strategy (set-shifting) and the orbitofrontal cortex (OFC) necessary for shifting attention between learned stimulus-outcome associations (reversal learning). The nucleus accumbens (NAc) is a major downstream target of both the mPFC and the OFC; however, its role in controlling reversal learning and set-shifting abilities is still unclear. Here we investigated the contribution of the two major NAc neuronal populations, medium spiny neurons expressing either dopamine D1 or D2 receptors (D1-/D2-MSNs), in guiding reversal learning and set-shifting in an attentional set-shifting task (ASST). Persistent inhibition of neurotransmitter release from NAc D2-, but not D1-, MSNs resulted in an impaired ability for reversal learning, but not set-shifting in male mice. These findings suggest that NAc D2-MSNs play a critical role in suppressing responding towards specific learned cues that are now associated with unfavorable outcomes (i.e. in reversal stages), but not in the suppression of more general learned strategies (i.e. in set-shifting). This study provides further evidence for anatomical separation of reversal learning and set-shifting abilities within cortico-basal ganglia-thalamo-cortical loops.